(untitled) (Eurasian Journal of Philology Science and Education, 2016)
In this article the author touches upon an autobiographism subject in Ivan Shchegolikhin’s works. It should be noted that in recent years I.P. Shchegolikhin fruitfully worked in the genres of the novel and story having pronounced autobiographical character. Noting pronounced autobiographism in Shchegolikhin’s works, the author also doesn’t miss from weed sight and unique genre specifics of the writer, to understand which it is possible, having considered creative history of his texts. In article it is said how the writer used two tendencies of classical realism: one of them it is closely connected with the Russian tradition of chronicles and the description of customs, the second – with the all-European canon of a narration about psychological development of the hero. Besides the author of article emphasizes also a special kind of the documentary novel of I. Shchegolikhin that isn’t free gives the chance to define similarity of the writer to Dostoyevsky.